Influence of light and gibberellin on the germination velocity of coffee seeds (Coffea arabica L.) - Resende, Maria de Lourdes; Silva, Tanismare Tatiana de Almeida; Guimarães, Renato Mendes; Silva, Edvaldo Aparecido Amaral da (Coffee Science - ISSN 1984-3909, 1970)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> There are various factors that interfere with seed germination. In this research the effect of light, gibberellins and paclobutrazol in coffee seed germination were evaluated. Seeds of coffee (Coffea arabica L.) from cultivar Rubi harvested at the developmental stage known as cherry were dried until 12% of water content. The first trial was performed in factorial design (2x2), the condtions being two (light and dark), presence and absence of gibberellins. The substrate was imbibed with 20ml of GA3 (100mM) and the control treatment with distillated water. The second trial was performed in factorial design (4x2x3), with four concentrations of paclobutrazol (0; 0,1;1,0; and 10 mM), two conditions (light and dark) and three storage conditions (0, 4 and 8 months). The substrate was imbibed with 20mL of paclobutrazol and the control treatment with distillated water. Both trials were performed in four replications of fifty seeds. Seed sowing was performed in gerbox tray with two blotting papers and one germitest paper. The dark condition was created by wrapping the gerbox with an aluminum foil. The germiantion velocity rate, germination at thirty days and the time to 50% root protrusion were evaluated. The gibberellin treatment in seed coffee decreases the germination velocity rate and percentage of germination. The gibberellin inhibitor decreases the gemination velocity rate but it did not reduce the effect of light. High values of germination velocity rate were observed in dark.